2021
DOI: 10.3389/fbioe.2021.664592
|View full text |Cite
|
Sign up to set email alerts
|

Host Response to Biomaterials for Cartilage Tissue Engineering: Key to Remodeling

Abstract: Biomaterials play a core role in cartilage repair and regeneration. The success or failure of an implanted biomaterial is largely dependent on host response following implantation. Host response has been considered to be influenced by numerous factors, such as immune components of materials, cytokines and inflammatory agents induced by implants. Both synthetic and native materials involve immune components, which are also termed as immunogenicity. Generally, the innate and adaptive immune system will be activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 248 publications
0
38
1
Order By: Relevance
“…In contrast to those findings, other studies indicate a direct correlation between an activation of the host immune system and the hydrophobicity of metallic alloys [ 6 , 29 ]. Seong and Matzinger hypothesise that exposed hydrophobic structures trigger a DAMP activated immune response [ 19 ].…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…In contrast to those findings, other studies indicate a direct correlation between an activation of the host immune system and the hydrophobicity of metallic alloys [ 6 , 29 ]. Seong and Matzinger hypothesise that exposed hydrophobic structures trigger a DAMP activated immune response [ 19 ].…”
Section: Discussioncontrasting
confidence: 61%
“…After immediate surface adsorption of blood proteins, the interaction of cells and the implant as well as the characteristics of the metallic surface have a great influence on the initial attachment process. This is mediated by integrin receptors, leading to adhesion as well as a primary immune response of the body [ 5 , 6 ]. It is well established in the literature that the surface microtopography such as roughness or micro-discontinuities, hydrophilicity/-phobicity, chemistry and charge influence molecular adhesion processes [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apparently, the scaffold MCH induces the secretory activity of MSCs to a greater extent than the tissue-specific scaffold DPC, whereas DPC is a stimulator for the formation of cartilage-like structures. It can be assumed that the differences in the functional activity of DPC and MCH scaffolds are based on the dependence of cell behavior on the elasticity, topography, and chemical composition of the carrier [27][28][29]. Interestingly, in a comparative study of gelatin gels with different rigidity, it was demonstrated that the gel with high rigidity promoted osteogenic differentiation of MSCs yet polarized macrophages towards the M1 phenotype, which is characterized by the production of proinflammatory cytokines [30].…”
Section: Stimulating Cartilage Regeneration In An Adjuvant Model Of Rabbit Knee Osteoarthritis Evolving Into Osteoarthrosismentioning
confidence: 99%
“…One major setback in tissue graft or organ transplant, from a donor of a different species from that of the recipient, is the possibility of zoonosis and immunological rejection [ 49 , 50 , 51 , 52 ]. The major concerns have been diseases, such as herpesviruses, retroviruses, Toxoplasma gondii [ 53 , 54 ], Mycobacterium tuberculosis, encephalomyocarditis virus [ 55 ].…”
Section: Introductionmentioning
confidence: 99%